Can Viewing Modality Affect Frontal Mandibular Bone Height Measurement? A Comparison Between 3D Digital Imaging and Communications in Medicine Viewer and Printed Portable Document Format Cone Beam Computer Tomography Reports - Michael Solomonov; Yoav Shapinko; Ella Lalum; Joe Ben Itzhak; Sapir Argaman; Matan Schottig; Amit Halpern; Nirit Yavnai; Idan Stiklaru (Dentistry Journal)
Objectives: Buccal cortical bone dimensions are crucial in dental radiology, as they impact orthodontic treatment outcomes. Changes in alveolar bone dimensions can result in malocclusion and require interdisciplinary approaches for correction. The accurate quantification of buccal bone dimensions is crucial for appropriate treatment planning and avoiding medico-legal issues. This study aimed to compare buccal bone height measurements between three-dimensional (3D) digital imaging and communications in medicine (DICOM) data and portable document format (PDF) cone beam computer topography reports for mandibular frontal teeth, testing the hypothesis of no difference in values between the two modalities. Methods: Each of the five observers performed a total of 720 height measurements (360 by DICOM and 360 by PDF), yielding a total of 3600 measurements overall. Results: Compared with the DICOM format, using PDF files was associated with a significantly greater rate of inability to carry out the measurements (8.8% vs. 3%, respectively, p < 0.001, chi-square). The average buccal bone height measured in the DICOM was 11.51 mm, which was significantly greater than the 10.35 mm measured in the PDF (p < 0.001). The mean height measured by the DICOM was consistently greater than that measured by the PDF, with highly significant differences in the findings of four of the examiners (p < 0.001). Conclusions: Viewing modality significantly affected the height of the buccal bone in the frontal mandibular area. Compared with the generated PDF reports, the 3D DICOM viewer performed better than the printed PDF and enabled more measurements in the target area.